ZnO nanostructures with tunable visible luminescence: Effects of kinetics of chemical reduction and annealing - Raji, R. (H. : ĐHQGHN, 2017)
Highly crystalline ZnO nanoparticles were synthesized using a co-precipitation method. The morphology and optical properties of these nanoparticles are found to be highly sensitive to the growth parameters such as the concentration of reducing agent and annealing temperature. Indeed, the concentration of the reducing agent can alter the morphology of nanoparticles from quasi-spherical to rod-like and then to flower-like structures. Attempts were made to tune the emission wavelength over the visible region by varying the kinetics of chemical reduction and annealing. The possibility of tuning the emission in a visible range from orange to red and then to green by changing the nature of defects by annealing is also reported. Analysis of the Raman spectrum, with its intensity observed at 580 cm-1 corresponding to E1(LO) mode, revealed that the kinetics and thermodynamics of formation and growth of these nano-particles determined the nature and density of the probable defects such as oxygen vacancies, interstitial zinc atoms and their complexes